Presença de achados ecocardiográficos compatíveis com cardiopatia congênita entre fetos de mães diabéticas e sua relação com os níveis plasmáticos maternos de frutosamina. - Karen Guimaraes Fuscaldi (2011)
Purpose: To study the occurrence of congenital cardiopathies atechocardiography in fetuses whose mothers had preexisting orgestational diabetes mellitus (DM) and to associate to plasma levels offructosamine during pregnancy. Patients and Methods: A register studycovering 126 Brazilian pregnant women (31,1±6.6 years old), in 2000-2007, that were submitted to routine fetal echocardiography by the samephysician, indicated because of DM during pregnancy. We analyzed thefirst dosage of plasma fructosamine during prenatal care (22.1±8.1 weeksof gestation) that was found in 91 medical records. The presence orabsence of structural or functional echocardiographic findings ofcongenital cardiopathy was associated with fructosamine plasma levels bylogistic regression. We assessed odds effect modification by maternal ageand insulin usage. Results: Sixty eight fetuses (54% of the 126 fetus)presented echocardiographic findings of congenital cardiopathy. Ten(14,7% of the 68 fetus) had functional echocardiographic findings ofcongenital cardiopathy. Fifty eight (85,3% of the 68 fetus) presentedstructural echocardiographic findings of congenital cardiopathy or both.Among structural echocardiographic findings of congenital cardiopathy,cardiomegaly of any cardiac chamber was the most frequent (n=33),followed by interventricular communication (n=21). Among the functionalones, the most frequent was pericardial effusion (n=7), followed bybradycardia (n=3). The mean maternal fructosamine plasma level washigher among pregnant women whose fetuses presented CCE than inthose whose fetuses did not (2.70±0.78mmol/L, 2.13±0.53mmol/L,respectively, p<0.0001). Crude Odds ratio for echocardiographic findingsof congenital cardiopathy and abnormal plasma fructosamine (>2.68mmol/L) was 7.0 (2.4-20.1, 95% CI, p<0.0001). Adjusted Odds ratio bymaternal age and insulin usage was 6.0 (1.9-18.6, 95% CI p= 0.002).Conclusions: An abnormal fructosamine plasma level increases thechances of having CCE among referral pregnant women with DM